Becoming an entrepreneur: opportunities and identity transitions. Issue 2 (13th June 2016) - Lewis, Kate V.; Ho, Marcus; Harris, Candice; Morrison, Rachel
Abstract : Purpose: This paper aims to report an empirically grounded theoretical framework within which to understand the role of entrepreneurial identity development in the discovery, development and exploitation of opportunity, and to elaborate on how these identity transitions both mobilise and constrain female entrepreneurs. Design/methodology/approach: A qualitative case study-based research design was used in this study. Primary and secondary data were collected from eight female participants (all of whom can be categorised as "mumpreneurs") and analysed to inform the theoretical framework that is the foundation of the paper. Findings: The authors describe how identity conflict, role congruence and reciprocal identity creation play a critical role in venture creation as a form of entrepreneurship. Drawing on the constructs of identification, self-verification and identity enactment, the authors build a theoretical framework for understanding entrepreneurial identity transitions in relation to opportunity-seeking behaviours. Research limitations/implications: The work is theoretical in character and based on a sample that, whilst rich in the provision of theoretical insight, is small in scope. Additionally, the sample is located in one geographical context (New Zealand) which likely has implications for the way in which the key constructs are perceived and enacted. Originality/value: This paper is an attempt to integrate conceptualisations of entrepreneurial identity development with opportunity-related processes in the context of venture creation. A holistic focus on identity transitions and their relevance to perception and action in relation to opportunity (the root of entrepreneurial behaviour) is novel; at this point, it is exploratory in intention and tentative in reach.